PERSEPSI DRIVER PADA LAYANAN GRAB DI KOTA BATAM - Yobel Cesar Silitonga; Michael Jibrael Rorong (Program studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Persada Indonesia YAI, 2021)
This research was conducted to find out the perception and Grab service to the drivers in Batam city. The research method used in this study is a qualitative method with a descriptive approach. The informants in this study were the Grab drivers in Batam city as many as five people by looking for characteristics that fit the research topic. The analytical technique used in this study was phenomenology which was based on the experience of informants in the field and drawing conclusions. The data collection technique in this study was conducted by interviewing Grab drivers in Batam city related to the topic of this research, observing in the Batam city area by making observations which showed that there were activities between the driver's office and operational service offices, as well as library studies conducted by researchers reading library books and used of previous research as reference material perception is obtained based on observation, understanding and experience of students through being online motorcycle taxi drivers. The results of the research found based on the perception of Grab drivers in Batam City towards Grab services is that the drivers are still experiencing difficulties. This research is considered able to help the continuity of driver activities while in the field.